2016
DOI: 10.1097/iae.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Location of Intraretinal and Subretinal Fluid as Prognostic Factors for the Outcome of Patients With Optic Disk Pit Maculopathy

Abstract: Fundoscopic and OCT features can help predict surgical outcome in optic disk pit maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
5
27
0
Order By: Relevance
“…Visual and anatomical progress over the follow-up period consistent with our study suggested that ILM peeling is probably not essential in the treatment of most cases of ODP-M. [9][10][11][12][13][14] Intraoperative gas is also believed to displace the retinal and subretinal fluid away from the macula. 19,20 A recent study has suggested that resolution of ODP maculopathy may be faster in patients with gas tamponade.…”
Section: Tablesupporting
confidence: 79%
See 4 more Smart Citations
“…Visual and anatomical progress over the follow-up period consistent with our study suggested that ILM peeling is probably not essential in the treatment of most cases of ODP-M. [9][10][11][12][13][14] Intraoperative gas is also believed to displace the retinal and subretinal fluid away from the macula. 19,20 A recent study has suggested that resolution of ODP maculopathy may be faster in patients with gas tamponade.…”
Section: Tablesupporting
confidence: 79%
“…12 Recent studies have generally reported no additional benefit from the laser in long-term success rates. [13][14][15][16] Our study also suggest that JLP may not be necessary for success of PPV for at least our follow-up period.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations